THE ROLE OF SCHOOL PRINCIPALS IN ENHANCING TEACHER PROFESSIONALISM AND EDUCATIONAL QUALITY: A CASE STUDY OF MTSN 3 KARANGANYAR - Fajar, Muhammad Amanah; Sukari, Sukari; Sulistyowati, Sulistyowati (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study is motivated by the limited number of comprehensive investigations into how principals’ leadership through their roles as educators, instructional leaders, innovators, and motivators shapes teacher professionalism and educational quality within the madrasah context. The purpose of this research is to describe the leadership practices of madrasah principals that effectively enhance teacher professionalism and to identify the challenges and strategies involved in their implementation. Employing a qualitative approach with a case study design, the study involved 11 purposively selected informants (one principal, six teachers, and four students). Data were collected through semi-structured interviews, participatory observations (field notes dated June 19 and 21, 2023), and school documentation. Data analysis followed the steps of data reduction, display, and conclusion drawing as outlined by Miles, Huberman, and Saldaña (2014), with source and technique triangulation used to ensure credibility. The findings indicate that the principal enacted an integrated leadership approach serving simultaneously as educator, leader, innovator, and motivator that directly supported the development of teachers’ pedagogical, professional, social, and personal competencies. However, the effectiveness of these efforts was hindered by issues related to teacher wellbeing, teachers’ dual workloads, and limited financial resources.